Puerperal uterine inversion-a near miss: case series - Malik, Sanjum Yasmin; Mittal, Arushi; Bhatia, Ruby; Tiwari, Vidhushi; Bansal, Komal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine inversion occurs when the uterine fundus collapses into the endometrial cavity, turning the uterus partially or completely inside out. It is a rare and severe complication with an incidence of 1:2000 to 1:50000 reflecting the quality of third stage of Labour. We studied case series of 4 cases on postpartum uterine inversion. We studied case series of 4 cases on postpartum uterine inversion in our hospital (MMIMSR), who were referred to us, from local hospitals with postpartum collapse in shock. Patient resuscitated with colloids and crystalloids, blood and blood products. Methods such as manual reposition of uterus have aided to reduce maternal morbidity and mortality in our cases. Hence early recognition and timely referral to a tertiary care hospital with ICU and blood bank facilities, helps to manage obstetrical emergencies. Acute uterine inversion is an obstetric emergency and can lead to the maternal mortality. Proper training of health care workers to conduct labour, institutional deliveries and active management of third stage of labour should be encouraged. Early diagnosis and appropriate management is the key to reduce maternal morbidity and mortality.